The Implementation of SWOT Analysis of People Economic Empowerment Business Loan (KUPEM) in Jambi Province - Desmaryani, Susi (Jurnal Bina Praja: Journal of Home Affairs Governance, 2016)
The problems of SMEs today are generally only able to survive but rarely oriented towards growth and capacity development of the company. One of the problems that hinder the growth of SMEs is financing problems. The government has tried to provide financing assistance in the form of soft loans, one of which is KUPEM, but SMEs do not have the commitment to running the business with loans that have been granted by the government. This study aims to determine the implementation strategy of People Economic Empowerment Business Loan (KUPEM) in the Province of Jambi. The research method used was a case study with descriptive research type. The sample consists of 125 respondents. Sampling is conducted in a nonprobability sampling and purposive sampling. Data were analyzed using SWOT analysis. The results showed that the implementation of KUPEM by the Provincial Government of Jambi through internal analysis indicates the value of the power factor is still below the weakness factor. External analysis of People Economic Empowerment Business Loan still has a big opportunity than a threat factor. Therefore, People Economic Empowerment Business Loan continues because it can help the growth of the community effort by making strategic changes. Result of the study recommend to strengthen internal factors which are the analytical skills of relevant agencies that are trusted to provide recommendations for KUPEM loans, (1) Relevant agencies create mentoring programs to enhance the ability of SMEs actors, (2) Through the relevant agencies forming a group of associations between groups of SMEs, (3) Increasing motivation to make MSMEs business through counseling activity, and improve the competence of field educators, (4) Conduct analysis of the suitability of business in accordance with local conditions (in this case the state of nature, the public taste and the target market).